European Macro-Regional Strategies and Approaches: Baltic Sea and Danube Experiences and the New Perspective for Adriatic-Ionian Cooperation - Bassetti, Caterina; Carteny, Andrea (Richtmann Publishing, 2012)
European Union aims to extend the stability and democracy area within and outside the current EU borders. To this purposethe reduction of inequalities between different regions represents one of the Union main goals. The Macro-Region strategy represents aninnovative pragmatic model of multilevel governance that involves in an open and shared dialogue all of the actors according to anintegrate approach: EU, States, regional and local authorities and the civil society. The authors trace the European legislative path in thisfield highlighting how the strategy could represent the sunset of the sector-based approach in the resolution of Macro-Regional urgentissues.